Posted by **NIHAL** on Sunday, July 10, 2011 at 10:10am.

prove that (x+y)^3-(x-y)^3-6y(x^2-y^2)=8y^3

## Answer this Question

## Related Questions

- maths - If the sum of the squares of the roots of the quadratic equation ax^2 + ...
- Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...
- Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...
- DISCRETE MATHS - Prove that for every set S, Ø \subseteq( S. i need to Use ...
- Maths - X and Y are points on the sides BC and AC of a triangle ABC respectively...
- Maths - prove that 2+2=5
- maths - prove that: 1/1+x^b-a + x^c-a + 1/1+x^a-b +x^a-c = 1
- maths - prove that : 2^n + 2^n-1 / 2^n+1 - 2^n = 3/2
- maths - If a+b+c=0 then prove that a^4+b^4+c^4=2(a^2b^2+b^2c^2+c^2a^2)
- maths - prove that 2 2 2 2 (n-1) + n + (n+1) = 3n +2